THE ROLE OF NIGERIAN SECURITY AGENCIES IN THE 2015 GENERAL ELECTIONS - Omede, Jolade; Ngwube, Arinze; Idowu, Aluko Opeyemi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Elections are critical to the success of any democracy just as security is an essential ingredient of successfully organized elections. Security is a determining factor on the part of election organizers, contenders for political offices and the electorate is in agreement to be the pre-condition for a successful process. It is practically impossible to hold credible elections in an insecure state. The involvement of the Nigeria police in the electoral processes in Nigeria is seen as a war-like situation by her citizenry. However, post-elections pose a further security threat. Its source of data is essentially secondary involving books, journals, articles related to the subject matter under review. Data sourced were qualitatively analyzed using descriptive method for data analysis and qualitative reporting. The paper examines the role of Nigeria security agencies in the 2015 election and recommended solutions.